PENGARUH PERILAKU BERFOTO DI OBYEK WISATA TERHADAP KEBAHAGIAAN WISATAWAN - Hastuti, Saptin Dwi Setyo (STP AMPTA Yogyakarta, 2017)
In these recent years, the prospect of photography is increasing. It also influences tourism industry. Photography also has important role in the development of tourism industry. This research aims to investigate (1) the factors influencing tourist’s behavior in taking photo, (2) the activities after taking photo, (3) and the influence of tourist’s behavior in taking photo towards their happiness. This research was a survey research. The locations of this research were in Malioboro, Hutan Pinus, Tebing Breksi, Kalibiru, and Gunung Api Purba Nglanggeran. The population comprised the visitors of those places. The sample was taken by applying sample non probability technique due to the unavailable visit data. The sample for each place was 80. Thus, the whole sample was 400. The survey was conducted on April – May 2017. The data were collected through questionnaire. The data were analysed by applying descriptive statistics and crosstab in the SPSS 16. The result of the research shows that the factors influencing the tourists’ photo behavior are the scenery or background of the place, the condition and completeness of facilities, the provided photo spot, the photo activity, and the access post photo. Furthermore, the result also shows that the activities after taking photo were the speed of publishing the photo, the editing, dan publishing photo in instagram. Last, the tourist’s taking photo behavior influencing the happiness were because of the reason of taking photo, taking photo at different spot, taking many photos, and the quality of the photo. Keywords : Tourism, Photo, Happiness